Peter Stalker, The Work of Strangers : A Survey of International Labour Migration. Ginebra, International Labour Office, 1994 - Castillo, Manuel Ángel (El Colegio de México A.C., 1999)
Peter Stalker, The Work of Strangers: A Survey of International Labour Migration, Ginebra, International Labour Office, 1994.